EFFECTS OF CIJI HUA’AI BAOSHENG FORMULA ON APOPTOSIS CORRELATION FACTORS OF TUMOR CHEMOTHERAPY MODEL MOUSE WITH H22 HEPATOMA CARCINOMA CELLS - Cheng, Yao; Xi, Shengyan; Wang, Yanhui; Gong, Yuewen; Xu, Yangxinzi; Shi, Mengmeng; Loy, Guanjie; Zhao, Xinyue (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Ciji Hua’ai Baosheng Formula (CHBF) is a traditional Chinese empirical formula that can help the tumor patients who received chemotherapy to antagonize the toxin and side-effects so as to improve and prolong the life. This study is to evaluate the effects of Ciji Hua’ai Baosheng Formula on apoptosis correlation factors of transplanted tumor chemotherapy model mouse with H22 hepatoma carcinoma cells through detecting the protein level of serum Bax, Bcl-2, Caspase-3, epidermal growth factor receptor (EGFR) and the protein expression of CyclinD1 in femur bone marrow. Materials and Methods: H22 hepatoma carcinoma cells were cultivated and diluted to 2×107/ml, and a total of 50 specific pathogen-free Kunming mice were injected subcutaneously into the right anterior armpit with H22 hepatoma carcinoma cells, after 7 days, all mice had formed tumors and were used peritoneal injection of Cytoxan (CTX) (200mg/kg) to establish the mouse chemotherapy model with transplanted tumor, then they were randomly divided into 5 groups such as model, positive control (CTX, 0.033g/kg) and three CHBF (117g/kg, 58.5g/kg and 29.25g/kg) groups with 10 mice in each group. They were administered next day after making model. Survival state was observed. After administering for 10 days, pathological tissue structural change was detected by light microscope, blood was collected through pricking eyeball, protein level of serum Bax, Bcl-2, Caspase-3 and EGFR was detected by enzyme-linked immunosorbent assay (ELISA), the protein expression of CyclinD1 in femur bone marrow was detected by immunohistochemisty. Results: Under the light microscope, the deteriorated degree of tumor tissue and the proliferation degree of tumor cells in three CHBF groups were obviously milder than that of model group. The protein content of the pro-apoptotic gene Bax and effective enzyme Caspase-3 in CHBF (58.5g/kg and 29.25g/kg) groups were obviously higher than that of model groups (P<0.05; P<0.01). The protein content of the apoptosis inhibitory gene Bcl-2 in three CHBF was obviously decreased than that of the model and CTX groups (P<0.01). The protein level of serum EGFR in three CHBF groups was decreased, and lower than that of model and CTX groups (P<0.05; P<0.01). The protein expression of CyclinD1 in femur bone marrow in CHBF (117g/kg and 58.5g/kg) groups was decreased obviously, which showed significant difference compared with model group (P<0.05; P<0.01). Effects of CHBF (117g/kg) on Bcl-2, Caspase-3, EGFR and CyclinD1 had more effective than effects of just single-use chemotherapy drug CTX (P<0.05; P<0.01). Conclusion: A certain concentration of Ciji Hua’ai Baosheng Formula can promote the expression of pro-apoptotic gene Bax and Caspase-3 and restrain the expression of apoptosis inhibitory gene Bcl-2, and reduce the promotive effect of EGFR and CyclinD1 on tumor cell proliferation to play a synergetic role on promoting apoptosis of the chemotherapy model mice of transplanted tumor with H22 hepatoma carcinoma cells, and parts of its possible mechanisms may be related with promoting tumor cell apoptosis and inhibiting proliferation.